Ultrathin and porous δ-FeOOH modified Ni3S2 3D heterostructure nanosheets with excellent alkaline overall water splitting performance. Issue 40 (9th October 2020) - Ji, Xuefeng; Cheng, Chuanqi; Zang, Zehao; Li, Lanlan; Li, Xiang; Cheng, Yahui; Yang, Xiaojing; Yu, Xiaofei; Lu, Zunming; Zhang, Xinghua; Liu, Hui
Abstract : Clarifying the catalytic mechanism of an FeOOH/Ni3 S2 heterogeneous catalyst for overall water splitting. Abstract : The design and synthesis of bifunctional heterostructure catalysts is significant to achieve excellent water electrolysis performance. Nevertheless, it remains a challenge to explore the exact active centers of the bifunctional catalysts in the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Herein, a bifunctional catalyst of ultra-thin porous δ-FeOOH modified Ni3 S2 nanosheets exhibits a relatively low overpotential of 187 mV for the OER and 106 mV for the HER at a current density of 10 mA cm −2, respectively. In addition, the overall water splitting unit provides a potential of 1.525 V at 10 mA cm −2 and maintains a performance of 96.85% after 24 h continuous testing. Multispectral analysis and density functional theory (DFT) calculations disclose that the constructed interface between δ-FeOOH and Ni3 S2 has two functional groups of Ni–O–Fe and Fe–S bonds to boost the OER and HER performance, respectively, thereby accelerating the overall electrochemical water splitting process in alkaline solution.